2022
DOI: 10.2147/copd.s353187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Digital COPD Education Program for Healthcare Professionals in Long-Term Care – A Mixed Methods Study

Abstract: Background Lack of routines and competence among healthcare professionals have been reported as barriers to COPD management in long-term care. Online education could be used as a strategy to make COPD education more accessible. Purpose The aim of this study was to evaluate a digital COPD education program for healthcare professionals in long-term care regarding feasibility, knowledge and working procedures. Methods A randomized controlled fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Moreover, we have previously reported that a digital COPD education program could be used to increase objective measures of COPD-specific knowledge among health care professionals involved in COPD management [ 46 ]. Although objective measures of COPD-specific knowledge were not obtained in this qualitative study, in the category “receiving competence support,” health care professionals expressed that the COPD Web offered a unified knowledge bank, which led them to receive a higher and broader level of competence regarding COPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we have previously reported that a digital COPD education program could be used to increase objective measures of COPD-specific knowledge among health care professionals involved in COPD management [ 46 ]. Although objective measures of COPD-specific knowledge were not obtained in this qualitative study, in the category “receiving competence support,” health care professionals expressed that the COPD Web offered a unified knowledge bank, which led them to receive a higher and broader level of competence regarding COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Interview times vary and, occasionally, are short. Still, we interpreted our data to be rich enough for the analysis performed here, and a specific duration is not a guarantee for richness [ 46 , 48 ]. Second, during the analysis, triangulation between authors was made to ensure that our interpretation was grounded in the empirical data [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, digital health technologies have emerged as effective solutions to help patients track their disease progression over time, including for patients with rare or orphan diseases [ 16 - 18 ]. Successful implementation of user-centered digital health interventions has improved patient’s quality of life across many common chronic conditions [ 19 , 20 ]. Some digital health apps and wearables for functional gastroenterological disorders such as Bowelle (Bowelle AB) and AbStats (Alpha Logic, Inc) have been developed; however, they only offer stand-alone tracking and symptomatic management, thus leaving a need for a multicomponent customized approach for patients with CVS [ 21 ].…”
Section: Introductionmentioning
confidence: 99%